2021
DOI: 10.1111/jcal.12545
|View full text |Cite
|
Sign up to set email alerts
|

Which way of design programming activities is more effective to promote K‐12 students' computational thinking skills? A meta‐analysis

Abstract: Promoting the cultivation of computational thinking (CT) skills in programming activities has become a key issue in the K‐12 curriculum, however, there is no unified conclusion on how to design programming activities to promote the acquisition of CT skills more effectively. The purpose of this study is to determine the effectiveness of using programming to enhance K‐12 students' CT skills and explore the influence of various programming instructional design factors on the acquisition of CT skills. This study p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 65 publications
1
50
0
1
Order By: Relevance
“…Meanwhile, BootUp's coding (Rich et al, 2021), hour of code (Quiterio Figueiredo, 2017), EasyLogic 3D (Rios Felix et al, 2020, intensive coding (Ozmutlu et al, 2021), computational thinking test (CTt) for beginners (BCTt) and TechCheck (Relkin et al, 2021), basic coding (Critten et al, 2021;Piedade et al, 2020), ACME 'Code Animation by Evolved Metaphors' (Mecca et al, 2021) and block programming activities (Silva et al, 2021) were used in developing CT skills. Furthermore, visual basics and pencil code (Deng et al, 2020), unplugged programming activities (Sun et al, 2021a(Sun et al, , 2021b and visual programming environments (Yi Wu & Yu Sheng, 2021) have all demonstrated to be helpful in improving CT skills in two ASEAN nations.…”
Section: Coding Programmingmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, BootUp's coding (Rich et al, 2021), hour of code (Quiterio Figueiredo, 2017), EasyLogic 3D (Rios Felix et al, 2020, intensive coding (Ozmutlu et al, 2021), computational thinking test (CTt) for beginners (BCTt) and TechCheck (Relkin et al, 2021), basic coding (Critten et al, 2021;Piedade et al, 2020), ACME 'Code Animation by Evolved Metaphors' (Mecca et al, 2021) and block programming activities (Silva et al, 2021) were used in developing CT skills. Furthermore, visual basics and pencil code (Deng et al, 2020), unplugged programming activities (Sun et al, 2021a(Sun et al, , 2021b and visual programming environments (Yi Wu & Yu Sheng, 2021) have all demonstrated to be helpful in improving CT skills in two ASEAN nations.…”
Section: Coding Programmingmentioning
confidence: 99%
“…CT is described by Wing (2006) as 'the mental processes involving framing problems including their solutions expressed in a way that an information-processing agent may successfully carry out'. There were many studies undertaken to eliminate the gap in CT (Sun et al, 2021b). As a consequence, many academics emphasise the need of including CT in the curriculum in regard to a 21st-century literacy at various education levels, starting from kindergarten to university (Abdullah et al, 2019;Jaipal-Jamani & Angeli, 2017;Nouri et al, 2020;Pei et al, 2018;Tasso et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the international context, there are two main methods for cultivating students' CT skills in programming classrooms: plugged-in and unplugged (Del Olmo-Muñoz et al, 2020;Sun et al, 2021b). Among them, plugged-in programming has been widely promoted and applied in K-12, and its effect has also been supported by sufficient evidence.…”
Section: The Teaching Of Computational Thinking: Programmingmentioning
confidence: 99%
“…The emphasis on CT has been spurred by seminal calls such as the ones put forth by Seymour Papert and Jeannette Wing, who highlighted the potential of CT to support analytical thinking, creativity and the development of critical thinking skills. Recently, there has been an increased emphasis on CT around the world, including discussions about integrating programming and CT in primary education curricula (Kong & Wang, 2021;Sun et al, 2021). At the same time, numerous technological products (e.g., software and robotic kits) have emerged aiming at supporting children to learn how to code (Jung & Won, 2018;Papadakis, 2020;Sullivan & Heffernan, 2016;Yu & Roque, 2019), and for developing the CT competencies needed in an ever-increasing technological world.…”
mentioning
confidence: 99%